ASHEED: Attention-shifting mechanism for depolarization of cluster head energy consumption in the smart sensing system. (1st October 2022) - Lu, Xu; Chen, Kezhou; Liu, Jun; Chen, Rongjun; Wu, Wanqing; Polat, Kemal; Alhudhaif, Adi; Alenezi, Fayadh; Althubiti, Sara A.
Highlights: An energy-consuming attention-shifting mechanism (ASHEED) is proposed. The ASHEED algorithm uses a competitive radius-based clustering method. The comprehensive performance of ASHEED algorithm is much better than RUHEED. Abstract: The sensing node clustering algorithm is a network topology control method that can effectively extend the lifetime of smart sensing systems (SSSMs). However, the traditional topology algorithms suffer from the excessively early death of cluster heads. Hence, the attention-shifting mechanism for energy consumption based on hybrid energy-efficient distributed clustering (HEED) is proposed in this paper, called attention-shifting hybrid energy-efficient distributed clustering (ASHEED). The energy consumption of the cluster heads are reduced by shifting data reception and fusion energy consumption of the cluster heads to other cluster member nodes (Agents) within its competitive radius. Agent selection is performed by communication energy consumption comparison to ensure the rationality of cluster heads and agent positions with the aim of reducing the communication energy consumption for re-clustering. Experiment results demonstrated that the proposed approach could maximize the balance of energy consumption of cluster heads and common nodes, maintain the integrity of the network, and extend the optimal operation time of SSSMs.